Ethical and legal considerations posed by patents in space innovation and commercialization in the EU - Markeviča, Darja (Riga Graduate School of Law, 2023)
The current legal framework surrounding space exploration and use is characterized by limitations and loopholes, hindering international collaboration. Ethical considerations also arise when patenting space-related inventions. The objective of this thesis was to explore the legal and ethical challenges associated with patenting space-related inventions in the European Union and propose strategies for overcoming these challenges. Key legal challenges include the harmonization of patent laws across jurisdictions and the establishment of distinct territorial boundaries for patent protection in outer space. The Outer Space Treaty's non-appropriation principle raises additional legal issues. The rise of private space exploration enterprises necessitates an adequate ethical framework to address monopolization concerns and preserve fair competition. Sustainability is also an important factor, with the industry promoting the reduction of environmental impact and the use of renewable resources. Future space-related technologies, such as space data management, space tourism, and space-based solar power, hold substantial innovation and commercialization potential. In order to realize this potential, it will be crucial to overcome legal and ethical obstacles.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Research Subject Categories::LAW/JURISPRUDENCE::Private law::Intellectual property law; space innovation